2017
DOI: 10.1021/acs.macromol.6b02284
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Dispersion Mechanism of Polymer-Grafted Nanorods in Polymer Nanocomposites: A Molecular Dynamics Simulation Study

Abstract: Coarse-grained molecular dynamics simulations are performed to investigate the dispersion behavior and the underlying dispersion mechanism of polymer-grafted nanorods (NRs) in a polymer matrix. The influences of grafting density, grafted chain length, and the miscibility between grafted chains and matrix chains are systematically analyzed. The simulation results indicate that the dispersion state of grafted NRs is determined primarily by the excluded volume effect of grafted NRs and the interface between graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 62 publications
3
38
0
Order By: Relevance
“…The strength of the interfacial interaction between nanoparticles and the polymer matrix can be tuned by surface functionalization, which has been shown to greatly influence the dispersion state of the nanoparticles and thus the mechanical properties of the conventional engineered nanocomposite. , While some effects on modulus and toughness can be observed here as well for aHNPs, when the whole design space is considered, our simulation results indicate that the ε pnp does not have a major influence on the modulus and toughness relative to other input parameters, as shown in Figure c. This observation is mainly due to the presence of covalent bonds between the nanoparticle and the grafted polymer chains, which limits polymer mobility while also preventing NP aggregation readily.…”
Section: Resultsmentioning
confidence: 68%
“…The strength of the interfacial interaction between nanoparticles and the polymer matrix can be tuned by surface functionalization, which has been shown to greatly influence the dispersion state of the nanoparticles and thus the mechanical properties of the conventional engineered nanocomposite. , While some effects on modulus and toughness can be observed here as well for aHNPs, when the whole design space is considered, our simulation results indicate that the ε pnp does not have a major influence on the modulus and toughness relative to other input parameters, as shown in Figure c. This observation is mainly due to the presence of covalent bonds between the nanoparticle and the grafted polymer chains, which limits polymer mobility while also preventing NP aggregation readily.…”
Section: Resultsmentioning
confidence: 68%
“…This nonmonotonic behavior of the rough nanoparticles’ dispersion/aggregation with changing monomer diameter is attributed to a competition of the available free volume gain of the polymer at the rough ridges of the nanoparticle and the entropic penalty to enter those rough ridges. Even though many simulation studies have focused on the morphology , and dynamics of nanorods in a polymer melt using coarse-grained models of nanorods with overlapping beads or connected coarse-grained beads, to the best of our knowledge, studies have not demonstrated how varying nanorod roughness resulting from varying extents of overlap in nanorod model beads impacts the phase behavior of nanorods in the polymer melt, which is addressed in this letter.…”
mentioning
confidence: 99%
“…The number of the grafted polymer chains is determined by the grafting density (Σ):Σ =normalN4πRNP2where N is the number of grafted chains per each NP (see Table S1, Supporting Information). When mapping the coarse‐grained bead‐spring model adopted in our simulation to real polymers by setting the diameter of the monomer σ = 1 nm, a grafting density of Σ = 0.3 corresponds to 0.298 chains per nm 2 , indicating a relatively dense brush …”
Section: Methodsmentioning
confidence: 99%
“…When mapping the coarse-grained bead-spring model adopted in our simulation to real polymers by setting the diameter of the monomer σ = 1 nm, a grafting density of Σ = 0.3 corresponds to 0.298 chains per nm 2 , indicating a relatively dense brush. [13] The grafted polymer chains are fully flexible and are represented by a generic bead-spring model, which was developed by Kremer and Grest. [14] Each grafted polymer chain contains 30 beads.…”
Section: Methodsmentioning
confidence: 99%